Validity of Mean Platelet Volume to Detect Hyperdestructive & Hypoproductive Thrombocytopenia in Tertiary Care Setting - Aslam, Wardah; Habib, Maryam; Dodhy, Mobina Ahsan; Shaheen, Masooma; Habib, Madiha (International Journal of Pathology, 2018)
Objective: Determine the validity of mean platelet volume (MPV) to detect hyper-destructive & hypoproductivethrombocytopenia, keeping bone marrow aspiration and biopsy as gold standard.Study Design: Cross sectional (Validation) study.Material and Methods: A total number of 147 patients of thrombocytopenia were enrolled.CBC of the patientwas done using an EDTA sample. Bone marrow aspiration and biopsy was also performed. Keeping aspirationresults as gold standard specificity and sensitivity of MPV was validated in diagnosing the type ofthrombocytopenia.Results: Mean platelet volume has a Sensitivity 95%, Specificity 15.7%, Positive Predictive Value64%, NegativePredictive Value 69.2% in detecting Hyper-destructive thrombocytopenia. It has a Sensitivity of 15.7%, Specificity95.5% with a Positive Predictive Value of 69%and Negative Predictive Value of 64% in detecting Hypoproductivethrombocytopenia.Conclusion: Mean platelet volume has limited sensitivity and specificity and can be used as an initial indicatorbut bone marrow aspiration and biopsy remains the gold standard for distinguishing between hyper-destructiveand hypo-productive thrombocytopenia.